Graphene mode-lockers for fiber lasers functioned with evanescent field interaction - Song, Yong-Won; Jang, Sung-Yeon; Han, Won-Suk; Bae, Mi-Kyung (AMER INST PHYSICS, 2010)
Employing graphene as an intracavity passive power modulating element, we demonstrate the efficient laser pulsation in high pulse-energy regime with evanescent field interaction between the propagating light and graphene layer. Graphene is prepared by the solution based reduction of graphene oxide, and dispersed homogeneously into the water for spray onto an all-fiber substrate, side-polished fiber. With the intracavity power up to 21.41 dBm, we ensure the robust high-energy operation without any thermal damage of graphene. Resultant output pulses have center wavelength, spectral width, and repetition rate of 1561.6 nm, 1.96 nm, and 6.99 MHz, respectively.